Diabetes and cognitive health in India: a nationally representative survey of adults aged 45 years and older - Lindsay C Kobayashi; Deborah A Levine; Jinkook Lee; David Flood; Hunter Green; Kenneth M Langa; Alden Gross; Caroline R Wixom (BMJ Open, 2025)
Objectives Most research on the relationship between diabetes and cognitive health has used data from high-income countries. This study described this relationship in India, the world’s most populous country.Design Cross-sectional analysis of the baseline wave of the nationally representative Longitudinal Ageing Study in India, conducted from 2017 to 2019.Setting All 36 Indian states and union territories.Participants 57 905 adults aged 45 years or older.Main outcome measures Scaled cognitive scores (mean of 0 and SD of 1) and cognitive impairment defined as a cognitive score 1.5 SD or below the age-matched and education-matched mean. Diabetes was defined as a self-report of a prior diabetes diagnosis made by a health professional or having a measured haemoglobin A1c ≥6.5%.Results In age-adjusted and sex-adjusted models, people with diabetes had cognitive scores that were 0.24 SD higher (95% CI 0.22 to 0.26) and had a 1.2% (95% CI 0.6% to 1.7%) lower prevalence of cognitive impairment than people without diabetes. Differences persisted even when adjusting for demographic, socioeconomic and geographical characteristics. Rural versus urban residence modified the relationships of diabetes with cognitive score (p=0.001) and cognitive impairment (p=0.003). In fully adjusted models, rural respondents with diabetes had 0.05 SD (95% CI 0.03 to 0.07) greater cognitive scores and 1.6% (95% CI 0.9% to 2.4%) lower prevalence of cognitive impairment than those without diabetes. In urban areas, respondents with and without diabetes had similar cognitive scores and prevalence of cognitive impairment.Conclusions Middle-aged and older adults with diabetes living in India had better cognitive health than those without diabetes. Rural versus urban area of residence modified this relationship. Urban–rural differences, the nutrition transition and social conditions likely influenced the cross-sectional relationship between diabetes and cognitive health in India, leading to different associations than reported in other countries.